Evolutionary targets of gene expression divergence in a complex of closely related pine species. Issue 1 (23rd August 2022) - Zaborowska, Julia; Perry, Annika; Cavers, Stephen; Wachowiak, Witold M.
Abstract: The environment is a powerful selective pressure for sessile organisms, such as plants, and adaptation to the environment is particularly important for long‐lived species, like trees. Despite the importance of adaptive trait variation to the survival and success of trees, the molecular basis of adaptation is still poorly understood. Gene expression patterns in three closely related, but phenotypically and ecologically divergent, pine species were analyzed to detect differentiation that may be associated with their adaptation to distinct environments. Total RNA of Pinus mugo, Pinus uncinata, and Pinus sylvestris samples grown under common garden conditions was used for de novo transcriptome assembly, providing a new reference dataset that includes species from the taxonomically challenging P. mugo complex. Gene expression profiles were found to be very similar with only 121 genes significantly diverged in any of the pairwise species comparisons. Functional annotation of these genes revealed major categories of distinctly expressed transcripts, including wood trait properties, oxidative stress response, and response to abiotic factors such as salinity, drought, and temperature. We discuss putative associations between gene expression profiles and adaptation to different environments, for example, the upregulation of genes involved in lignin biosynthesis in the species, which have adapted to mountainous regions characterized by strong winds and thick snow cover. Our study provides valid candidates for verification of the importance of the gene expression role, in addition to evidence for selection within genomic regions, in the process of ecological divergence and adaptation to higher altitudes in pine taxa. Abstract : The expression profiles of annotated (in color) and not annotated (in gray) gene models that discriminate three European pine taxa. The upper (A) panel shows markers significantly upregulated in tests comparing two mountain pines ( Pinus mugo and Pinus uncinata ) with their close relative, Scots pine ( Pinus sylvestris ); the lower (B) panel presents markers with differential expression between the two mountain pines.